Two Bronze Tritons from Nicolaes Witsen’s Collection - Halbertsma, Ruurd; Scholten, Frits (The Rijksmuseum Bulletin, 2017)
It recently emerged that two bronze ‘doorknobs’ in the Rijksmuseum collection, decorated with Tritons blowing conch shells and with inlaid silver discs, came from the renowned collection of the Amsterdam merchant and burgomaster Nicolaes Witsen. They were listed in 1728 in the catalogue of the sale of his estate (in the Antiquiteyten section) and appear in an engraving in the third, enlarged edition of Witsen’s Noord en Oost Tartaryen of 1785. It was also possible to establish that they were not, as had long been thought, sixteenth-century objects, but Roman appliques dating from the first century AD. The pair probably came from a litter used to carry the body of a deceased to its burial place. The two pieces were recently transferred to the National Museum of Antiquities in Leiden, where they have been reunited with other antiquities from Witsen’s collection.